APOE4 status influences the amyloid and tau relationship: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Dincer, Aylin; Gordon, Brian A.; Keefe, Sarah J.; Flores, Shaney E.; Schultz, Stephanie A.; Paulick, Angela M.; Feldman, Rebecca L.; Shady, Kristine E.; Hornbeck, Russ C.; Zhou, Yun; Morris, John C.; Benzinger, Tammie L.S.
Abstract: Background: The apolipoprotein E ε4 (APOE4) allele is a well‐established genetic risk factor for late‐onset Alzheimer disease (AD). There is strong evidence that APOE4 enhances amyloid accumulation and previous research in animal models have demonstrated that APOE4 promotes tau pathology independently of amyloid. In this study, we investigate the relationship between APOE4 and tau to see whether the relationship between APOE4 and tau is mediated by, independent of, or interacts with levels of amyloid. Method: 347 participants from the Knight Alzheimer Disease Research Center (mean age = 69.7) underwent tau‐PET imaging with [ 18 F]‐flortaucipir and amyloid‐PET with [ 18 F]‐florbetapir within a year. Tau‐ and amyloid‐ PET data were converted to standardized uptake value ratios (SUVRs) for each region of interest. A summary amyloid measure was calculated for statistical analysis using the average of lateral orbitofrontal, medial orbitofrontal, rostral middle frontal, superior frontal, superior temporal, middle temporal, and precuneus regions. APOE4 carrier status was defined by the presence of at least one ε4 allele. We ran three separate linear models for our analysis. First we examined the APOE4‐tau and the amyloid‐tau relationship with model 1 predicting regional tau using amyloid, age, and sex as predictors and model 2 predicting regional tau using APOE4 status, age, and sex as predictors. Next we examined the relationship between tau and both APOE4 and amyloid in concert with model 3 predicting regional tau using amyloid, APOE4 status, an interaction between amyloid and APOE4 status, sex, and age as predictors. Result: We found that the amyloid‐tau relationship was widespread throughout the brain and the APOE4‐tau relationship was predominately in the inferior parietal and temporal pole regions (figure 1). Most importantly, we found a significant APOE4 status and amyloid interaction that was most prominent in the entorhinal cortex and superior temporal regions (figure 2). Conclusion: Our results show that there is a significant effect of APOE4 status and tau deposition that is above and beyond the effect of APOE4 on amyloid. This relationship is synergetic, where E4 carriers have more tau pathology for the same levels of amyloid deposition as non‐carriers.